To do justice : the civil rights ministry of Reverend Robert E. Hughes - Jimerson, Randall C. (Religion and American culture (Tuscaloosa, Ala.), 2022)
"The biography "A Civil Rights Activist from Montgomery to Zambia: The Career of Reverend Robert E. Hughes" by Randall C Jimerson examines the inter-racial nature of civil rights and liberation movements in Alabama, Southern Rhodesia, and Zambia and connects them on a global scale through the life and career of Revered Robert E. Hughes"--